Factors Influencing The Unachievement of ODF Status in Tingkis Village, Singgahan Subdistrict, Tuban District - Sholikah, Amilus; Has, Dwi Faqihatus Syarifah; Mindiharto, Sestiono; Inayah, Zufra (Yayasan Ahmad Mansyur Nasirah, 2024)
Tingkis Village has access to healthy latrines only 52%, and open defecation behavior to the river is 48%. This study aimed to analyze the factors that influence the unachievement of ODF status in Tingkis Village, Singgahan Sub-district. The research design was a cross-sectional survey with an observation approach. The population was 950 households in Tingkis Village. The sample size was 282 respondents taken by simple random sampling. The independent variables consisted of knowledge, attitude, economic status, ownership of healthy latrines, and commitment of village-level stakeholders, while the dependent variable was the unachievement of ODF status. Instruments used questionnaires on knowledge, attitude, economic status, ownership of healthy latrines, and observation sheets/checklists on the commitment of village-level stakeholders and the unachievement of ODF status. Analysis used Multiple Logistic Regression tests at a 95% confidence level (p<0.05). The research results show that the study showed that knowledge had a p-value of 0.000 < 0.05, attitude with a p-value of 0.033 < 0.05, economic status with a p-value of 0.016 < 0.05, ownership of healthy latrines with a p-value of 0.016 < 0.05, the commitment of village-level stakeholders with a p-value of 0.003 < 0.05, and knowledge had the highest Exp(B) value (34.198) compared to other variables. The conclusion is knowledge, attitude, economic status, ownership of healthy latrines, and commitment of village-level stakeholders have an influence on the achievement of ODF status, and knowledge is the most dominant factor influencing the achievement of ODF status.